Projeto e desenvolvimento de um sistema de aquisição e armazenamento de dados para avaliações de máquinas agrícolas - Rosa, Lucas Simon da (2019)
In an agricultural production system, the most versatile machine is the tractor, mainly used for move and pull machines and attachments. The use of independent data collection and storage equipment or datalogger in the evaluation of agricultural machines made it possible to evaluate parameters and results that aim to optimize the energy consumed as a function of the work performed. Initially performed with analog datalogger, based on the operation of mechanical systems and with paper graphical recording of only one physical phenomenon in relation to time. With the emergence of microcontrolled electronic datalogger, electronic sensors, and nonvolatile storage devices, it has become extremely versatile equipment and can record multiple physical effects simultaneously. Datalogger have a high acquisition cost and often fulfill standard signal collection functions, which often do not meet the requirements of certain studies that lead researchers to develop their own collection devices, usually based on microprocessor-based electronic card development platforms. As a method to identify the desirable requirements, a search of articles over the last 22 years was carried out in the Capes Journals search platform with the keywords “datalogger” and “data logger”, obtaining 1,166 results, being selected the articles that had collectors data used outdoors, on agricultural machines or exposed to vibration, from these, were determined the types of sensors and signals most recurring, the rate of collection and resolution and protection from environmental factors, as well as the demand for new features that meet to technological advancement, which is entitled Baitalogger prototype.